PENGARUH EKSTRAK BIJI KAPAS (Gossypium hirsutum L.) TERHADAP REPRODUKSI MENCIT BETINA (Mus musculus L., Swiss Webster) - Novriyanti, Ernie; Sumarmin, Ramadhan; Zayani, Nofri; Ramadhani, Siska Adelya (Sainstek : Jurnal Sains dan Teknologi, 2014)
The aim of this experimental study is to know the effect of cottonseed extracts toward the reproduction of mice (Mus musculus L., Swiss Webster). This experiment used completely randomized design with 4 treatment and 6 replied. Treatment given was cottonseed extract with several dose, namely control (0 gram/mice), 0,03 gram/mice, 0,05 gram/mice and 0,07 gram/mice. This research was conducted on Desember 2013-January 2014 in animal house Zoology Laboratory Majors Biology FMIPA UNP. The parameters are vaginal smear, corpus luteum number, implantation, life fetus, died fetus, abnormal fetus, resorpsion fetus and average of weight fetus. Data is analyzed by ANOVA and DNMRT significant p (0,05). The result shows that cottonseed extract indicated that there are extension proestrous, metestrous, and diestrous. It can conclude that cottonseed extract influenced mice cycle reproduction. The cottonseed extracts indicated there are decreasing corpus luteum number, implantation number, life fetus number and average of fetus weight were compared by control. This research concludes that cottonseed extract (Gossypium hirsutum L.) influenced the performance reproduction of mice (Mus musculus L., Swiss Webster). Key words: gossypol, fetus, cycle and performance reproduction